Integrating Islamic Business Ethics in Labor Protection and Minimum Wage Determination in Indonesia - Ikhsan, Muhammad Miftahul; Nuraeni, Neni; Meiriyanti, Deffa (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2024)
Policies related to the minimum wage are a contentious issue in employment across both developed and developing countries, aiming to meet community needs and benefit families. However, a research gap exists in applying justice and moral principles to wage determination from the perspective of Sharia economic law in Indonesia. This study aims to analyze fair wage components according to Islam and the role of business ethics in protecting workers and determining wages. Employing a literature review method, data were gathered from various sources such as books, journals, and previous research findings, which were reviewed and analyzed using descriptive analysis techniques. The study emphasizes the importance of justice and moral components in Islamic wage determination, rooted in the absolute essence granted by God, essential for morality. Business ethics in work protection and wage determination are crucial to ensure fair treatment and prevent exploitation. Recommended steps include optimal labor protection and wage determination, timely payment of agreed wages, recognition and guarantee of labor, fair wage determination without harm, and providing worker freedom. The study's novelty lies in integrating Islamic principles of justice and morality into minimum wage policies and developing practical business ethics guidelines for labor protection and wage determination under Sharia economic law in Indonesia.